Pengaruh Citra Merek, Strategi Pemasaran Media Sosial, dan Minat Beli Terhadap Keputusan Pembelian - Nurul Annisyak, Wika; Ali, Ali (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the influence of brand image, social media marketing strategy, and purchase intention on purchasing decisions at Yuforia Cafe. A quantitative approach using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method is employed in this research. The study population consists of Yuforia Cafe customers who have purchased products or engaged in interactions with Yuforia Cafe, either directly or through social media, with a total of 109 respondents. Data collection was conducted using a probability sampling technique with a cluster random sampling approach. The analysis results indicate that social media marketing strategy and purchase intention have a significant influence on purchasing decisions. Conversely, brand image does not show a significant effect on purchasing decisions. These findings highlight the importance of social media marketing strategies in driving consumer purchasing decisions. Furthermore, companies can utilize these results to design more effective marketing strategies to enhance consumer engagement.